Multidimensional structural linguistic analysis of moves in abstracts: A corpus-based approach - Hasliza Binti Abdul Halim, Ahmad AL-shorman, Manvender Kaur Sarjit Singh, (Opción, 2019)
This paper reports a multidimensional move analysis and identifies metadiscourse features of abstract sections of 30 Scopus-indexed articles in the Social Sciences and identifies the interactive stylistic resources used by the authors. The results show that the authors used various interactive resources, to help readers understand a text. Among the resources are: explaining, orienting and guiding the readers through the discourse. Also by using interactive metadiscourse, the authors organize the main contents by considering readers‟ knowledge, experiences and needs through transitions, which indicate how the authors intend the connections between elements of the discussion to be comprehended